Utworzenie Kasy Oszczędności w Wolnym Mieście Krakowie i jej działalność w latach 1844-1857 - Mataniak, Mateusz (Czasopismo Prawno-Historyczne, 2018)
The article presents the activity of the Savings Bank in Cracow between 1844 and 1857. It recreates the course of works undertaken during its creation by the Representatives Assembly. The basic ideological assumptions on which it was based were shown. Moreover, the paper presents the participation in the creation process of the Brotherhood of Mercy and of the Mount of Piety (Latin Mons Pietatis). The legal basis of the Savings Bank’s functioning was analyzed in detail. The foundation had the shape of statutory law from the 3rd of July 1844, the organization of the Management of the Savings Bank, the rules of depositing and withdrawing the savings, keeping accountancy and its control by the authorities. Also detailed data was included pertaining to the size of the deposit and the size of the withdrawal made from the Savings Bank. The basis of the article consists of the archival materials from the National Archive in Cracow and of the announcements made by the Management of the Savings Bank, which were published in “The Governmental Gazette”.